1988
DOI: 10.1103/physrevlett.61.547
|View full text |Cite
|
Sign up to set email alerts
|

Mean-Field to Tricritical Crossover Behavior near theSmecticASmecticC*Tricritical Point

Abstract: Precise x-ray measurements of the tilt angle near the smectic-^4-smectic-C* tricritical point show clear evidence of mean-field to tricritical crossover behavior; the mean-field region shrinks to zero at the tricritical point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…This binary mixture exhibits AC * transition which is between first order (pure C7) and second order, as observed experimentally [1,2]. A tricritical point (TCP) exists in this binary mixture for its AC * transition.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…This binary mixture exhibits AC * transition which is between first order (pure C7) and second order, as observed experimentally [1,2]. A tricritical point (TCP) exists in this binary mixture for its AC * transition.…”
Section: Introductionmentioning
confidence: 71%
“…As the concentration increases in a binary mixture of liquid crystals, a first order smectic A-smectic C (AC) or AC * transition changes toward a second order one, as observed experimentally in some binary mixtures such as C7 + 70PDOB [1,2], C7 + 10.O.4 [3,4] and SCE9 + SCE10 [5]. This has been demonstrated using the mean field models with the biquadratic coupling (P 2 θ 2 ) [6,7] and P 2 θ 2 + Pθ (bilinear) coupling in our recent studies [8][9][10][11], in particular for the binary mixtures of C7 + 10.O.4 [8], SCE9 + SCE10 [9,10] and C7 + 70PDOB [11].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…11 Compounds having high polarization ͑P s ͒ were considered to exhibit a first order Sm C * -Sm A phase transition. 12,14,15 Experimentally, it was shown that the Sm C * -Sm A phase transition was mainly driven by intermolecular forces producing the Sm C * phase. [16][17][18] However, some compounds having a smaller Sm A phase 10 or no Sm A phase 19 and small P s have also shown a second order Sm C * -Sm A phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…The first is the coupling of the tilt to biaxiality, which in chiral systems is related to the size of spontaneous polarization [3,4]. The second is the width of the A phase [5].…”
mentioning
confidence: 99%